Decolonizing Mathematics Curriculum and Pedagogy: Indigenous Knowledge Has Always Been Mathematics Education. Issue 1 (2nd January 2022) - Garcia-Olp, Michelle; Nelson, Chris; Saiz, LeRoy
Abstract: This article illustrates the shared work of Indigenous scholars and community members rooted in Indigenous knowledge toward the goal of decolonizing mathematics education. Furthermore, this study highlights IndigiLogix: Mathematics|Culture|Environment (M|C|E) programming, which is a mathematics precollege program created to advance college access and community empowerment for Indigenous students. IndigiLogix programming seeks to decolonize mathematics education through 4 curricular examples rooted in Indigenous place-based education, with the components of belonging, mastery, independence, and generosity (BMIG), and Indigenous mathematics knowledge. In partnership with public schools' Indian Education Departments and Indigenous community Elders and community members, this model was employed in a precollege mathematics program for Indigenous youth.